2009
DOI: 10.1163/106311109x12474622855101
|View full text |Cite
|
Sign up to set email alerts
|

Individual Difference and Study-Specific Characteristics Influencing Attitudes about the Use of Animals in Medical Research

Abstract: Research has shown that both individual diff erence characteristics (e.g., sex, attachment to pets) and study-specifi c characteristics (e.g., type of animal used) infl uence the extent to which people support or oppose the use of animals in research. Th e current study examined how three studyspecifi c characteristics (type of animal used, level of harm to the animal, and severity of the disease being investigated) infl uenced attitudes toward the use of animals in biomedical research. Participants read one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…These findings are consistent with the suggestion that justifiability is based on a combination of familiarity, phylogeny, and capacities, with different emphasis between students and faculty [30,[35][36][37]. A similar pattern of unequal species-based acceptability of animal research has been reported in other studies as well [18,24,25,31,[38][39][40]. As for purpose, men scored higher than women on justifiability for each species, but student-faculty differences were not significant after accounting for other variables.…”
Section: Plos Onesupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with the suggestion that justifiability is based on a combination of familiarity, phylogeny, and capacities, with different emphasis between students and faculty [30,[35][36][37]. A similar pattern of unequal species-based acceptability of animal research has been reported in other studies as well [18,24,25,31,[38][39][40]. As for purpose, men scored higher than women on justifiability for each species, but student-faculty differences were not significant after accounting for other variables.…”
Section: Plos Onesupporting
confidence: 89%
“…The Ipsos MORI surveys also reported greater acceptance of medical research than testing of chemicals [27]. Other studies have addressed animal research acceptability as a function of experimental purpose, and identify rankings similar to ours, especially lower support for testing of household chemicals or cosmetics [18,24,30,31]; reviewed in [32]. For faculty, justifiability of the study of animal disease, basic research, human disease, and testing human medicines were only slightly different from one another, while for students they were more separated.…”
Section: Plos Onesupporting
confidence: 62%
See 1 more Smart Citation
“…(3) Most of the scenarios we used focused on medical research, which is the most accepted area of animal experimentation [ 10 , 13 , 28 , 29 ]. Additionally, no species was used in the scenarios which is known to be less accepted (like dogs or non-human primates) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Most of the scenarios we used focused on medical research, which is the most accepted area of animal experimentation [ 10 , 13 , 28 , 29 ]. Additionally, no species was used in the scenarios which is known to be less accepted (like dogs or non-human primates) [ 28 ]. Instead, most scenarios stated the use of rodents which are generally the most accepted group for animal experimentation, according to previous surveys [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%